The Influence of Social Media TikTok and E-wom Interested to Buy Soemethinc Brand and Impact on The Purchace Decision (Survey of TikTok Users in The Management Study Program of University Perjuangan Tasikmalaya) - Rade Handayani; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (Journal of Indonesian Management, 2022)
This study aims to determine the effect of TikTok and E-WOM social media on buying interest in the Somethinc brand and their impact on purchasing decisions (a survey of TikTok users, students of the Management Study Program, University Perjuangan Tasikmalaya). The method used is a quantitative approach with the survey method. The sampling technique used is non-probability sampling by purposive sampling. The sample used in this study were 100 respondents. The respondents in this study were required to be who were students of the Management Study Program at the Perjuangan Tasikmalaya university who were TikTok users, 18 – 23 years old and have seen promotions or content of Somethinc brand at least once .The results of this study indicate that social media TikTok has a significant effect on purchasing decisions through buying interest in the Somethinc brand to TikTok users. E-wom has a significant effect on purchasing decisions through buying interest in the Somethinc brand to TikTok users. Social media TikTok and e-wom influence purchasing decisions through buying interest..